Detection and identification of Xanthomonas arboricola pv. pruni from symptomless plant material: results of an Italian test performance study. (April 2015) - Loreti, S.; Pucci, N.; Perez, G.; Catara, V.; Scortichini, M.; Bella, P.; Ferrante, P.; Giovanardi, D.; Stefani, E.
<x xml:space="preserve">Abstract</x> Xanthomonas arboricola pv. pruni, the causal agent of bacterial spot disease of stone fruits, is a regulated quarantine pathogen in the European Union, listed as an A2 pest by the European and Mediterranean Plant Protection Organization (EPPO). Because detection and identification of this pathogen is key for its management and to ensure the production of pest free propagation material, it should be based on reliable tests, in particular when dealing with symptomless material. The current EPPO diagnostic Standard (PM 7/64) does not provide specific molecular methods for detection of this pest. The present paper summarizes the results of a test‐performance study (TPS) to validate, at a national level, a detection procedure for this bacterium. A working group was established in order to evaluate the performance criteria for tests included in the current EPPO Standard, and for a conventional PCR. On the basis of the obtained performance criteria, a diagnostic procedure was elaborated and then applied to perform an inter‐laboratory comparison. Screening tests for the detection of the bacterium on symptomless plant material based on IF and/or PCR were proposed, in parallel with isolation on agar media. For identification two methods were suggested: a molecular test or IF. This paper reports on the results of the TPS and proposes a flow diagram for the detection and identification of X. arboricola pv. pruni.